Synthesis, Spectral and Antimicrobial Studies of Some Co(II), Ni(II) and Cu(II) Complexes Containing 2-Thiophenecarboxaldehyde Moiety - A. P. Mishra; A. Tiwari; S. K. Gupta; Rajendra Jain (E-Journal of Chemistry)
Some new Schiff base metal complexes of Co(II), Ni(II) and Cu(II) derived from 3-chloro-4-fluoroaniline (HL1) and 4-fluoroaniline (HL2) with 2-thiophenecarboxaldehyde have been synthesized and characterized by elemental analysis, FT-IR, FAB-mass, molar conductance, electronic spectra, ESR and magnetic susceptibility. The complexes exhibit coordination number 4 or 6. The complexes are colored and stable in air. Analytical data revealed that all the complexes exhibited 1:2 (metal: ligand) ratio. FAB-mass data show degradation pattern of the complexes. The Schiff base and metal complexes show a good activity against the bacteria; B. subtilis, E. coli and S. aureus and fungi A. niger, A. flavus and C. albicans. The antimicrobial results also indicate that the metal complexes are better antimicrobial agents as compared to the Schiff bases.